About the Medialogical Understanding of the Concept of “Book Culture” - S. V. Kozlov; I. V. Lizunova (Библиосфера, 2024)
The concept of “book culture”, which entered the domestic book-study discourse in the 1980s, is currently one of the central ones for both historical-book and theoretical-book studies. However, it has not yet received a conventional definition in Russian science. The purpose of the article is to formulate a definition of book culture based on the interpretative theory of culture and theoretical and methodological achievements of medialogy dominating in modern socio-humanitarian knowledge. The authors show the general theoretical context of the formation of the concept of “book culture”. The necessity of a pragmatic turn in theoretical book studies is substantiated. The possibilities of theoretical models of the media researcher G.M. McLuhan and the historian of the printed book R. Darnton for the interpretation of the concept of “book culture” are revealed. The author offers his own definition of book culture as a space of communication between various social actors, mediated by materialized texts broadcasting socially significant information.